KDRT DALAM PERKAWINAN KANONIK Tinjauan Yuridis - Robertus Rubiyatmoko (Litbang STFT Widya Sasana Malang, 2008)
Domestic violence usually happens because of wrong understanding on human dignity and family life. Violence against wife or husband or children is a concrete prove that a couple excludes the essential ends of marriage, which are the good of spouses (bonum coniugum) and the good of offspring (bonum prolis) as mentioned in canon 1055§1 of the Code of Canon Law. Therefore, domestic violence which is occurred from the beginning of marriage, makes the marriage invalid. According to the Code of Canon Law, the parties have a right to process an anullement of their marriage based on domestic violence as caput nullitatis. This article seeks to study the so called KDRT (violence in family) from the perspective of the Canon Law and its implication to possibility of anullement of marriage.